The EndoRotor®: endoscopic mucosal resection system for non-thermal and rapid removal of esophageal, gastric, and colonic lesions: initial experience in live animals - Hollerbach, Stephan; Wellmann, Axel; Meier, Peter; Ryan, Jeffery; Franco, Ramon; Koehler, Peter (Endoscopy International Open, 2016)
Background and study aims: The EndoRotor® is a novel, non-thermal, automated mechanical endoscopic resection system designed to remove benign mucosal neoplastic tissue throughout the gastrointestinal tract. It uses suction pressure to pull in mucosa and rapidly and precisely cut it while automatically transporting the samples to a collection trap for later histologic evaluation.Patients and methods: To study the technical properties and therapeutic potential of this new tool, we performed multiple upper and lower gastrointestinal endoscopic mucosal resections in three healthy live pigs. Animals were anesthetized and kept artificially ventilated while two physicians performed multiple qualitative mucosal resections on various sites of the pigs’ esophagus, stomach, duodenum, and colon.Results: Rapid resection of flat and slightly elevated mucosa up to several centimeters in size/diameter was performed. No major bleeding occurred during and after resections. When used properly, no gastrointestinal wall perforations occurred during superficial resections. Perforations in the colon were only observed when the device was deliberately pushed against deeper sub-mucosal layers or when exceptional force was applied to penetrate the gastrointestinal wall. Histologic specimens showed complete mucosal removal at resection sites. The flexible catheter could be moved and directed towards most of the areas of interest in the gastrointestinal tract.Conclusion: The EndoRotor rapidly and easily resects flat and slightly elevated gastrointestinal mucosa with a short learning curve. Future studies in humans should be performed to prove its ability for large-area mucosal resections in benign conditions such as laterally spreading adenomas in the colon, or Barrett’s mucosa in the distal esophagus.